Empowerment of the Urban Poor by Social Services in the Town of Pekanbaru - Siti Rohimah; Muslim Muslim (Penerbit Jurnal Indonesia, 2024)
Poverty is a very complex and multidimensional phenomenon. As far as the background of this research is concerned, poverty will lead to the emergence of social impacts. The purpose of this study is to analyze the empowerment program carried out by the social services of the city of Pekanbaru in combating poverty. To find out the implementation of the social service program of the new town in empowerment of urban poor communities, there are four indicators that are the benchmark, namely human building, enterprise building, institution building, and environment building. The type of researcher used in this study is qualitative with a descriptive approach. Data collection techniques with interviews, observations and documentation. As a result of research, poverty can be eradicated through PKH programmes, BPNT, disability building and UMKM building. Obstacles in empowering urban poor communities are: inadequate targeted assistance, lack of knowledge and knowledge in the use of technology in UMKM construction, and poor service obtained by people with disabilities